Comparison of Duhamel’s Pull-Through Procedure Versus Soave’s Pull Through Procedure for The Management of Hirschsprung’s Disease: Duhamel’s Pull-Through Versus Soave’s Pull Through Procedure - Haider, Naveed Haider; Hameed, Soban; Binet Mansoor, Khola; Huda Abbasi, Hassan; Mahmood, Zahid; Naveed, Khadija; Saleem, Javeria (Pakistan Journal of Health Sciences, 2023)
The Hirschsprung’s disease is managed via surgical procedures. Mostly two different procedures are common called Soave’s and Duhamel’s. we compared the procedure safety and output benefits and complications rate of these two studies. Objectives: To find the efficacy of Soave’s and Duhamel’s pull-through procedure that which method is more safe and efficient for the children with Hirschsprung’s disease. Methods: Randomized clinical trials were conducted. The sample included was consists of 60 children of less than 1 year of age up to 3 years. Sample size was calculated by world health sample size calculator for randomized control trials. With the confidence interval of 95%. Purposive sampling technique was used to collect the data. The study used paired t-test to compare the outcomes of two surgical procedures. 30 patients got Soave’s procedure and 30 underwent Duhamel’s procedure. Overall 54 boys and 6 girls were under study. Paired t-test were used to analyze the data. Results: In Soave’s pull-through the 26 patients recovered without any serious complications. If we compared this to the Duhamel’s procedure output the complications rate was a little high 23 patients recovered uneventfully while complications reported in 7 patients. The results of this study prove the significant findings in terms of efficiency and associated complications. Conclusion: In the light of above mentioned clinical trials the Soave’s procedure covers less frequency of complications and cost-efficient in comparison to Duhamel’s pull-through procedure in which the complications rate was significantly higher and a costly procedure.